Pengaruh Konsep Tri Kaya Parisudha Dan Kompetensi Sumber Daya Manusia Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi Dengan Sistem Pengendalian Internal Sebagai Variabel Pemoderasi: Studi Kasus Pada Lembaga Perkreditan Desa Se-Kecamatan Kerambitan - Dewi, Ni Kadek Yuni Candra; Kusumawati, Ni Putu Ayu; Andayani W, Rai Dwi (Hita Akuntansi dan Keuangan, 2024)
This study aims to examine the concept of Tri Kaya Parisudha and the competence of human resources that influence the occurrence of accounting fraud tendencies, where there is also an internal control system that has a direct effect as moderation. This research was conducted at the Village Credit Institution (LPD) in Kerambitan District using a questionnaire and involving 75 respondents. The data analysis method used is SEM PLS with the help of Smart PLS software. The results showed that (1) the concept of Tri Kaya Parisudha has a negative and significant effect on the tendency of accounting fraud. (2) The competence of human resources has a negative and significant effect on the tendency of accounting fraud. (3) The internal control system is able to moderate (strengthen) the relationship between Tri Kaya Parisudha and the tendency of accounting fraud. (4) The internal control system is capable of moderating (weakening) the relationship between human resource competence and the tendency of accounting fraud.